Investment Opportunities Through BSI Cicil Emas Financing Product - Aisyah, Esy Nur; Hermawan, Bagus (Universitas Nusantara PGRI Kediri, 2024)
Research aim : This research aims to determine what creates opportunities for long-term investment through the BSI Cicil Emas Financing product at Bank Syariah Indonesia, Turen Malang Sub-Branch Office. Design/Methode/Approach : This qualitative research method uses a descriptive approach with data collection techniques using interviews, documentation and observation. Research Finding : The research results show that the BSI Cicil Emas financing product has the opportunity to become a long-term investment instrument because of the ease of applying for financing, the benefits of investing in gold, and the ease of buying and selling gold, precious metals, the continued increase in gold prices and low competition.